The revenge of geography : what the map tells us about coming conflicts and the battle against fate - Kaplan, Robert D., 1952- (New York : Random House, 2012)
The insights, discoveries, and theories of great geographers and geopolitical thinkers of the past look back at critical pivots in history and then look forward at the evolving global scene.
From Bosnia to Baghdad -- The revenge of geography -- Herodotus and his successors -- The Eurasian map -- The Nazi distortion -- The Rimland thesis -- The allure of sea power -- The'crisis of room' -- The geography of European divisions -- Russia and the independent heartland -- The geography of Chinese power -- India's geographical dilemma -- The Iranian pivot -- The former Ottoman Empire -- Braudel, Mexico, and grand strategy.
Includes bibliographical references (pages [349]-378) and index.
Keywords: Political geography